2016
DOI: 10.1038/srep32310
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of diverse graphene nanomeshes based on simultaneous regulation of pore size and surface structure

Abstract: Recently, graphene nanomesh (GNM) has attracted great attentions due to its unique porous structure, abundant active sites, finite band gap and possesses potential applications in the fields of electronics, gas sensor/storage, catalysis, etc. Therefore, diverse GNMs with different physical and chemical properties are required urgently to meet different applications. Herein we demonstrate a facile synthetic method based on the famous Fenton reaction to prepare GNM, by using economically fabricated graphene oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…The observed G band is clearly asymmetric which, on the lower wavelength side of the peak in nanoscale systems, is usually associated with the phonon confinement 49 , thus suggesting that the particle size is sufficiently small for bulk phonon dispersion description to break down. It is worth pointing out, that our glucose CNDs samples show Raman signal very similar to that observed in graphene oxide 50 53 , which may suggest significant contribution of out-of-plane bonding.…”
Section: Resultssupporting
confidence: 72%
“…The observed G band is clearly asymmetric which, on the lower wavelength side of the peak in nanoscale systems, is usually associated with the phonon confinement 49 , thus suggesting that the particle size is sufficiently small for bulk phonon dispersion description to break down. It is worth pointing out, that our glucose CNDs samples show Raman signal very similar to that observed in graphene oxide 50 53 , which may suggest significant contribution of out-of-plane bonding.…”
Section: Resultssupporting
confidence: 72%
“…Experimental work on GNM's currently achieves pore diameters as small as 3 nm. [23] Therefore, we have to consider multiple dopants per pore, studying the details of their packing and stability for near term applications. These studies also provide a framework for understanding the behavior of dopant ionic complexes for chemical separation applications.…”
Section: Description Of the Physical Systemmentioning
confidence: 99%
“…[17] GNMs have been fabricated by several groups, with pore-size distributions in the 3-200 nm range. [21][22][23][24] A study of the I-V characteristics of p-doped GNM-based transistors indicated that their ON-OFF ratio is an order of magnitude larger than that of pristine graphene, but with lower electrical conductivity. Most recently, sub-nanometer pores were fabricated, albeit without the periodicity necessary for transport application.…”
Section: Introductionmentioning
confidence: 99%
“…However, driving these redox reactions of oxygen functional groups needs necessarily conductive network (sp 2 carbon) in RGO, especially at high scan rates. Therefore, the specific surface area, oxygen concentrations, and electrical conductivity of RGO play crucial roles in electrochemical performance for supercapacitors …”
Section: Introductionmentioning
confidence: 99%